THE EFFECT OF CONSUMER TRUST AND USE OF ONLINE OJEK SERVICES ON PURCHASE OF FOOD THROUGH THE MESSAGE BETWEEN GRABFOOD FEATURE IN COMMUNITIES IN DKI JAKARTA (NON THOUSAND ISLANDS) - Mufidah, Gina (Faculty of Economics and Business, Universitas Negeri Jakarta, 2022)
Purchasing food through the Grabfood delivery feature for people in DKI Jakarta is determined and influenced by many factors. This study aims to determine the effect of consumer trust and the use of online motorcycle taxi services on purchasing food through the Grabfood delivery feature for people in DKI Jakarta (non-thousand islands). This research is a quantitative research. The object of this study is the people of DKI Jakarta aged eighteen and over using the Grabfood delivery feature, with an unknown population. The sample in this study amounted to 115 respondents determined using the Malhotra formula. The analytical method used in this study is multiple regression analysis. The results of this study indicate that consumer trust and the use of online motorcycle taxi services have a partial effect on food purchases. The variables of consumer trust and the use of online motorcycle taxi services simultaneously have a positive and significant effect on food purchases.